CYBERSECURITY AS A SOCIAL PHENOMENON (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Global informatization currently actively controls the existence and life of states of the world community, information technologies are used to solve problems of ensuring national, military, and economic security, etc. At the same time, one of the fundamental consequences of the global informatization of state and military structures has become the emergence of a fundamentally new environment of confrontation between competing states - cyberspace, which is not geographical in the generally accepted sense of the word, but is fully international.